The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1177/0022022116680480
|View full text |Cite
|
Sign up to set email alerts
|

Language Brokering, Prosocial Capacities, and Intercultural Communication Apprehension Among Latina Mothers and Their Adolescent Children

Abstract: Past research on language brokering has primarily focused on the positive and negative outcomes that children of immigrant families experience from brokering. Little is known, however, regarding the positive experiences that language brokees—the immigrant family members for whom children broker—garner from participating in this interaction. Utilizing survey data from 120 Latina/o mother–adolescent dyads, we examined whether more frequent participation in brokering was positively related to mothers’ (i.e., brok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
(91 reference statements)
0
9
1
Order By: Relevance
“…Recent research suggests that the process of enculturation has the potential to be problematic for the health and well-being of Latino immigrant adolescents (Kam, Guntzviller, & Pines, 2017; Kam & Lazarevic, 2014b). In particular, adolescent children tend to be interpreters for their parents both in terms of the language and cultural expectations and as a result, parents often rely on their children to navigate for their parents (Guntzviller, Jensen, & Carreno, 2017; Kam, Basinger, et al, 2017; Kam & Lazarevic, 2014a).…”
Section: Parentification and Family Communication In Immigrant Familiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research suggests that the process of enculturation has the potential to be problematic for the health and well-being of Latino immigrant adolescents (Kam, Guntzviller, & Pines, 2017; Kam & Lazarevic, 2014b). In particular, adolescent children tend to be interpreters for their parents both in terms of the language and cultural expectations and as a result, parents often rely on their children to navigate for their parents (Guntzviller, Jensen, & Carreno, 2017; Kam, Basinger, et al, 2017; Kam & Lazarevic, 2014a).…”
Section: Parentification and Family Communication In Immigrant Familiesmentioning
confidence: 99%
“…Most of parentification research, to date, has been conducted from the perspective of family counseling psychology and therapy (Champion et al, 2009; Hooper et al, 2012; Kuperminc et al, 2013) while very few communication studies investigated language brokering as a type of parentification (Guntzviller et al, 2017; Kam, Basinger, et al, 2017; Kam, Guntzviller, et al, 2017). Yet, previous findings indicate that parent–adolescent communication plays a key role during the process of emotional parentification (Kuperminc, Jurkovic, & Casey, 2009; Shin & Hecht, 2013; Telzer & Fuligni, 2009), less is known about how parents, particularly Mexican immigrant mothers, manage their private information with their children during the process of emotional parentification.…”
Section: Parentification and Family Communication In Immigrant Familiesmentioning
confidence: 99%
“…Past research has found some links between empathy and language brokering. Kam, Guntzviller, and Pines (2017) found that, among Latino adolescents, the path from brokering frequency to intercultural communication apprehension was mediated by empathic concern (i.e., sympathy and compassion for others), indicating that empathic concern may lessen the anxiety over communicating with people from different cultural backgrounds. Similarly, Guan et al (2014) reported that, among diverse, languagebrokering, undergraduate students, there was a bi-directional relationship between empathic concern and brokering for others besides the parents.…”
Section: Empathy Related Findings and Language Brokeringmentioning
confidence: 94%
“…In the research literature, feelings about language brokering can be summed as focused around three core experiences: efficacy, role reversal, and burden (Kim et al, 2014). Previous research suggests that efficacy, role reversal, and burden may interact with language brokering frequency to predict some outcomes like risky behaviors (Kam & Lazarevic, 2014), but may not moderate the relationship between language brokering frequency and prosocial capacities like empathy (e.g., Kam, Guntzviller, & Pines, 2017). Instead, positive and negative feelings have been found to directly relate to psychological correlates and outcomes.…”
Section: Feelings When Language Brokeringmentioning
confidence: 99%
“…Moreover, apprehensive individuals have trouble transitioning to new life events, including college (Hall & Scharp, 2018). High levels of communication apprehension are also associated with lower levels of compassion (Salazar, 2016), empathetic concern (Kam et al, 2017), and persuasive self-efficacy (Daly & Thompson, 2017).…”
Section: Introductionmentioning
confidence: 99%